2014
DOI: 10.1371/journal.pone.0106961
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Implementation of a Pilot Model for the Bidirectional Screening and Joint Management of Patients with Pulmonary Tuberculosis and Diabetes Mellitus in Mexico

Abstract: BackgroundRecently, the World Health Organisation and the International Union Against Tuberculosis and Lung Disease published a Collaborative Framework for the Care and Control of Tuberculosis (TB) and Diabetes (DM) (CFTB/DM) proposing bidirectional screening and joint management.ObjectiveTo evaluate the feasibility and effectiveness of the CFTB/DM in Mexico. Design. Prospective observational cohort. Setting. 15 primary care units in 5 states in Mexico. Participants: Patients aged ≥20 years diagnosed with DM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
8
16
0
4
Order By: Relevance
“…The proportion of new DM cases 64 (4.9%) identified in our study is similar to the study done in India (5%) [ 30 ], but higher than from China (3%), Gujarat-India (4%), Saluru–India (3.2%), Kolar–India (2.9%) and Mexico (4.4%) [ 25 28 , 31 ] and lower than the study finding in Trivandrum-India (7%) [ 32 ]. The relatively high proportion of undiagnosed DM in the study may indicate the magnitude of the disease, low awareness, lack of access to DM services, the importance of DM screening among TB patients which is crucial for early diagnosis and treatment of the two comorbid conditions [ 18 – 19 , 27 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of new DM cases 64 (4.9%) identified in our study is similar to the study done in India (5%) [ 30 ], but higher than from China (3%), Gujarat-India (4%), Saluru–India (3.2%), Kolar–India (2.9%) and Mexico (4.4%) [ 25 28 , 31 ] and lower than the study finding in Trivandrum-India (7%) [ 32 ]. The relatively high proportion of undiagnosed DM in the study may indicate the magnitude of the disease, low awareness, lack of access to DM services, the importance of DM screening among TB patients which is crucial for early diagnosis and treatment of the two comorbid conditions [ 18 – 19 , 27 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, this study assessed the status of glucose control only by medical records documented by a nurse or physician prior to treatment of TB 32. One prospective study suggested that joint management of TB and DM improve clinical outcomes 33. However, in this study, the control groups were extracted from the previous National Register of Cases of TB.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate increases with HbA1c level and diabetes duration, especially in patients with HbA1c over 9.0% and with diabetes duration over 10 years [ 16 ]. Another symptom screening research in Mexico detected 38 TB cases in 7,763 diabetes patients and 11 of them were unaware of their TB [ 17 ]. These studies pointed out that active screening and better glucose control might be important in TB prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors have been associated with TB, such as male gender [ 1 ], cigarette smoking [ 3 , 4 ], alcohol consumption [ 5 ], underweight [ 6 ], renal disease [ 7 ], household contact [ 8 ], socioeconomic status [ 9 ], and diabetes mellitus [ 10 ]. As diabetes patients increased year by year, more and more studies focused on TB prevention in diabetic group in these years [ 10 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation